1997
DOI: 10.1523/jneurosci.17-12-04591.1997
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Estrogen-Responsive Genes in Neuroblastoma SK-ER3 Cells

Abstract: To evaluate the role of estrogen receptor in the differentiation of cells of neural origin, we developed a molecular approach aimed at the identification of estrogen target genes by mRNA differential display PCR (ddPCR) in human neuroblastoma SK-ER3 cells. More than 3000 RNAs were examined, a few of which displayed a differential regulation pattern in response to 17␤-estradiol (E 2 ). Sequence analysis of three differentially amplified ddPCR products showed homology with the growthassociated nuclear protein pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 60 publications
2
40
0
2
Order By: Relevance
“…This increase was not observed with the antiestrogen TOT. Similarly Garnier et al, using differential display report that PTa mRNA expression was also enhanced in neuroblastoma cells after estrogen treatment (Garnier et al, 1997). The present studies now show that the increase in PTa mRNA in the presence of E 2 is also evident at the protein level.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This increase was not observed with the antiestrogen TOT. Similarly Garnier et al, using differential display report that PTa mRNA expression was also enhanced in neuroblastoma cells after estrogen treatment (Garnier et al, 1997). The present studies now show that the increase in PTa mRNA in the presence of E 2 is also evident at the protein level.…”
Section: Discussionsupporting
confidence: 84%
“…Their studies indicate the involvement of two half-EREs in the regulation by estrogens. These halfEREs, located at 7886 to 7861 and 7588 to 7560, were also proposed (but not examined) by Garnier et al (1997) to be involved in estrogen regulation of PTa expression in neuroblastoma cells. While mutational analyses support the involvement of these two halfEREs (Martini and Katzenellenbogen, 2001), the halfEREs were not cloned upstream of a heterologous promoter to indicate enhancer activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many experimental studies examined the responsiveness of DA neurons to estrogens and showed that estradiol levels induces DA synthesis and release, as well as DA neurons differentiation ( [57,58,81,151,171]). Importantly, MPTP caused greater DA depletion in male compared with female mice [59]; moreover, treatment with estradiol prevented the reduction in DA concentrations and the activation of glia in the striatum of animals treated with MPTP ( [31,59,169,235]).…”
Section: Estrogens and Parkinson's Diseasementioning
confidence: 99%